2021
DOI: 10.3390/nu13124532
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Potassium Excretion, Fibroblast Growth Factor 23, and Incident Hypertension in the General Population-Based PREVEND Cohort

Abstract: High plasma fibroblast growth factor 23 (FGF23) and low potassium intake have each been associated with incident hypertension. We recently demonstrated that potassium supplementation reduces FGF23 levels in pre-hypertensive individuals. The aim of the current study was to address whether 24-h urinary potassium excretion, reflecting dietary potassium intake, is associated with FGF23, and whether FGF23 mediates the association between urinary potassium excretion and incident hypertension in the general populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…Therefore, it was expected that a high sodium chloride supply combined with a high potassium intake (as in group HNaCl) would cause a decrease in serum FGF23. This hypothesis was also supported by findings from Yeung et al (2021), who observed an inverse correlation between renal potassium excretion and serum FGF23 in humans [ 67 ]. Despite a higher potassium and sodium supply, plus increased renal potassium excretion in the HNaCl group, no effect on serum FGF23 values was seen in cats.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, it was expected that a high sodium chloride supply combined with a high potassium intake (as in group HNaCl) would cause a decrease in serum FGF23. This hypothesis was also supported by findings from Yeung et al (2021), who observed an inverse correlation between renal potassium excretion and serum FGF23 in humans [ 67 ]. Despite a higher potassium and sodium supply, plus increased renal potassium excretion in the HNaCl group, no effect on serum FGF23 values was seen in cats.…”
Section: Discussionsupporting
confidence: 72%